Social Inclusion in Education: A Study of Access and Equality among Marginalized Groups - Sianipar, Godlif (PT. Anagata Sembagi Education, 2025)
Inequality in access to education in Indonesia remains a serious challenge, particularly for marginalized groups such as children from poor families, people with disabilities, and indigenous communities. Although the national legal framework guarantees the right to education, the reality on the ground shows that various structural and cultural barriers still hinder the creation of substantial educational equity. This research uses a qualitative approach with a case study method at an inclusive public school in a rural area to explore the implementation of social inclusion in the local context. Data were obtained through interviews, observations, and documentation studies, then analyzed thematically to uncover the dynamics of marginalized student participation, teacher readiness, and local community support. The results show that despite the commitment to inclusion, its implementation is still hampered by minimal teacher training, a lack of disability-friendly infrastructure, and the dominance of homogenous values in the learning system. However, the involvement of local actors and the use of a community-based approach have proven effective in strengthening the application of inclusive principles contextually. This research emphasizes that social inclusion is not merely an administrative effort but requires comprehensive structural and cultural changes. Therefore, a transformative and human rights-based education strategy is needed to realize an education system that is equitable, participatory, and truly respects diversity.